Brain delivery of quercetin-loaded exosomes improved cognitive function in AD mice by inhibiting phosphorylated tau-mediated neurofibrillary tangles. (1st January 2020) - Qi, Yao; Guo, Lin; Jiang, Yibing; Shi, Yijie; Sui, Haijuan; Zhao, Liang
Abstract: It is reported that quercetin (Que) can prevent tau pathology and induce neuroprotection by improving cognitive and functional symptoms in the treatment of Alzheimer's disease (AD). However, its clinical application has been limited due to its poor brain targeting and bioavailability. Exosomes are considered as cargo carriers for intercellular communication and especially serve as a natural and important drug brain delivery platform for achieving better treatment of central neurological diseases. Here, we developed plasma exosomes (Exo) loaded with Que (Exo-Que) to improve the drug bioavailability, enhance the brain targeting of Que and potently ameliorate cognitive dysfunction in okadaic acid (OA)-induced AD mice. Our results showed that Exo-Que improved brain targeting of Que as well as significantly enhanced bioavailability of Que. Furthermore, compared with free Que, Exo-Que better relieved the symptoms of AD by inhibiting cyclin-dependent kinase 5 (CDK5)-mediated phosphorylation of Tau and reducing formation of insoluble neurofibrillary tangles (NFTs), suggesting its therapeutic potential for better treatment of AD.